2015
DOI: 10.17795/jjcdc-29345
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Women’s Motivations for Seeking Health Information: A Qualitative Study

Abstract: Background: Today empowerment of women by health literacy has become a necessity. Researchers have shown that women are active seekers of health information and seeking behaviors are driven by various motivational factors. Paying attention to women's motivations for seeking health information could facilitate evidence-based policy making in promotion of public health literacy. As health information seeking develops within personal-social interactions and also the health system context, it seems that a qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…A study in the Netherland showed that women who had obtained pre-pregnancy health information were more likely to modify lifestyle behaviors than those who were not prepared for pregnancy [ 3 ]. Some other studies from different countries have reported the same findings; altogether confirming that pregnant women’s access to online maternal health information could encourage them to choose a healthier life style, which in turn improves maternal health [ 9 , 11 , 16 , 20 , 26 , 41 ]. Overall, the present study showed that online health information-seeking behavior does not have a positive relationship with lifestyle behaviors during pregnancy.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A study in the Netherland showed that women who had obtained pre-pregnancy health information were more likely to modify lifestyle behaviors than those who were not prepared for pregnancy [ 3 ]. Some other studies from different countries have reported the same findings; altogether confirming that pregnant women’s access to online maternal health information could encourage them to choose a healthier life style, which in turn improves maternal health [ 9 , 11 , 16 , 20 , 26 , 41 ]. Overall, the present study showed that online health information-seeking behavior does not have a positive relationship with lifestyle behaviors during pregnancy.…”
Section: Discussionsupporting
confidence: 60%
“…In this regard, a qualitative study in China reported that support for lifestyle modifications during pregnancy was one of the most important benefits of using the Internet from the perspective of pregnant women [ 20 ]. Another qualitative study in Iran has also shown that promoting a healthy lifestyle is one of the main reasons for Iranian women to seek online health information [ 26 ]. However, the overall effect of searching online pregnancy-related information on the actual changes in lifestyle during pregnancy has remained controversial.…”
Section: Introductionmentioning
confidence: 99%
“…4 The importance of paying attention to women's motivation in seeking health information is important, because it can facilitate fact-based policy making to improve the family's health status, the realization of public health understanding and achieve optimum health results. 14…”
Section: Mothers' Behavior In Utilizing Smartphonesmentioning
confidence: 99%